The perception of accounting students about the competences of the accountant (Revista Brasileira de Contabilidade e Gestão, 2021)
This study aimed to analyze the perception accounting students about the competences of the accountant. According to the methodology, this research is classified as quantitative, in relation to the approach, descriptive, as to the objectives and with regard to the procedures, it is a survey research. As a data collection instrument, a questionnaire was applied, based on research by Faotto and Jung (2018), Wollinger, Martins and Marinho (2018), Moura and Lima Filho (2019) and Silva et al. (2020), containing 11 (eleven) closed questions, validated by professors in the area and applied electronically in the period between August and September 2020. The population of this article was 335 students enrolled in 2020/2 in accounting of the community university in Santa Catarina, resulting in a sample of 111 respondents, representing 33.13% of the population. The collected data were tabulated using Google Forms® and descriptive statistics were used as a data analysis technique, according to the distribution of relative frequency. As main results, it can be observed that the perception of students about the competences of the accountant is in line with the provisions of Resolution CNE/CES 10, of December 16, 2004, which established the national curriculum guidelines for the accounting course. It was also found that the accounting course prepares its students adequately, demonstrating which skills and competencies they should develop and improve, with the aim of becoming accountants able to work in the labor market for the benefit of society as a whole.
Keywords: Competencies; Accounting Professional; Graduation; Accounting Sciences